Improving neural prosthetic system performance by combining plan and peri-movement activity - Yu, B.M.; Ryu, S.I.; Santhanam, G.; Churchland, M.M.; Shenoy, K.V. (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2004)
While most neural prosthetic systems to date estimate arm movements based solely on the activity prior to reaching movements during a delay period (plan activity) or solely on the activity during reaching movements (peri-movement activity), we show that decode classification can be improved by 56% and 71% respectively by using both types of activity together. We recorded from the pre-motor cortex of a rhesus monkey performing a delayed-reach task to one of seven targets. We found that taking into account the time-varying structure in peri-movement activity further improved performance by 15%, while doing the same for plan activity did not improve performance. We also found low correlations in activity between pairs of simultaneously-recorded units and across time periods within a given trial condition. These results show that decode performance can be significantly improved by combining information from the plan and peri-movement periods, and that there is nearly no loss in performance when assuming independence between units and across tune periods within a given trial condition.